The Role of Intestinal Microbiota in Atopic Dermatitis - Wen Zuo; Cai-Hong Sun (Wolters Kluwer Health, 2022)
The early intestinal microbiota plays an important role in immune regulation, and the unbalanced composition may increase the occurrence of allergic diseases, including atopic dermatitis. This review summarizes the latest studies in the occurrence and development of intestinal microflora and its relationship with atopic dermatitis. These results are conducive to understand the differences in the composition of intestinal microbiota between patients with atopic dermatitis and healthy people, and provide a potential intervention for prevention or treatment of atopic dermatitis.